Attainment of individual and organisational goals in industries: implications for occupational social worker (2009). (2009)
The proliferation of human service programmes and the emergence of the social work profession in the workplace soften the distraction between the world of work (aiming at production goals) and world of employees (individual employees and their families). The role of social work became clearer in industries and became centered on job-related problems, individual problems that require therapy, casework services and family issues. Social workers now counsel employees on a wide range of personal, family and social problems, present policy positions on community relations to corporate executives, mediate in disputes; develop and conduct stress management programmes and assist on issues of layoffs and retirement. The paper concludes that occupational social workers will continue, both now and in future, to balance the world of work with the world of the family for effective and efficient survival of both the employees and the employers.